Interlanguage Analysis of Indonesian Young Learner’s English Acquisition - Like Raskova Octaberlina (PANYONARA: Journal of English Education, 2022)
The current trend of ELT in Indonesia is to learn English at young age. Young learners are perceived as more successful language learners compared to those learning English in their adulthood. This article aims at analyzing interlanguage variations of Indonesian young learners, serving as evidence of their English acquisition. The findings showed that Indonesian young learners of English have not been able to produce tense-marking verb, and omit some grammatical morphemes such as –s iending in simple present tense, and –s ending in possessive. The interlanguage variations are influenced by L1 transfer, overgeneralization and simplification. It is expected that the findings contribute to better comprehension of Indonesian learners’ English acquisition..